2009
DOI: 10.1080/13547500902730672
|View full text |Cite
|
Sign up to set email alerts
|

Manganese exposure among smelting workers: blood manganese–iron ratio as a novel tool for manganese exposure assessment

Abstract: Unexposed control subjects (n = 106), power distributing and office workers (n = 122), and manganese (Mn)-exposed ferroalloy smelter workers (n = 95) were recruited to the control, low and high groups, respectively. Mn concentrations in saliva, plasma, erythrocytes, urine and hair were significantly higher in both exposure groups than in the controls. The Fe concentration in plasma and erythrocytes, however, was significantly lower in Mn-exposed workers than in controls. The airborne Mn levels were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 36 publications
4
71
0
2
Order By: Relevance
“…Increased concentrations of MnB have been frequently observed in exposed vs non-exposed workers, for example in welders 21 and in smelter workers. 25,26 We determined about 10 mg/l as median MnB in German welders that was similar to the average concentration reported for US welders in bridge building 27 but lower than in Korean welders (15.5 mg/l). 28 A lower average concentration of 8.6 mg/l in Russian welders might be explained by a longer time lag between shift exposure and blood sampling.…”
Section: Discussionsupporting
confidence: 80%
“…Increased concentrations of MnB have been frequently observed in exposed vs non-exposed workers, for example in welders 21 and in smelter workers. 25,26 We determined about 10 mg/l as median MnB in German welders that was similar to the average concentration reported for US welders in bridge building 27 but lower than in Korean welders (15.5 mg/l). 28 A lower average concentration of 8.6 mg/l in Russian welders might be explained by a longer time lag between shift exposure and blood sampling.…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, a straight correlation between air concentration of Mn and blood serum level of Mn was seen in this study, and as compared to Bast-Pettersen et al study, the exposure to manganese particles in the air with concentration of 301 μg/m 3 proved the direct correlation with manganese concentration in the blood, and urine of exposed workers (181 mmol/l and 0.9 nmol/mmol creatinine, respectively) [28]. The research was done by Cowan et al to report that the concentration of manganese in the inhaled air of exposed workers had a significant relationship with the ratio of Mn/Fe of erythrocytes (r = 0.77, p < 0.01) and the workers' blood plasma (r = 0.7, p < 0.01) [30]. Other researchers' finding was higher than this research finding for Mn in air and blood level but a straight relationship was seen between air-Mn and B-Mn (serum).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the biological half-life of manganese in the human body against 20-40 days, and after this period the amount of manganese in the workplace decreased or normal serum level would return. Given the daily ongoing additional amounts in the period, that had been inserted into the body through the urine, were excreted [18,24,30]. According to the textbook by Zenz [15], the main way to enter Mn pollutants into the human body is through inhaled manganese, and the lungs and human brain are the target and any metabolism in other organs of the body and organs were not the one.…”
Section: Discussionmentioning
confidence: 99%
“…At most, biological measurements of Mn, such as blood, hair, or toenail concentrations, may possibly indicate short-term Mn exposure. [45][46][47][48] These may not provide reliable dose estimates, and it is debatable whether short-term exposure is as relevant as cumulative (lifetime) exposure in studies focused on PS.…”
Section: Discussionmentioning
confidence: 98%